Implementasi Program Pembinaan Kepribadian Untuk Anak Didik Pemasyarakatan - Muh. Shofiyuddin; Yuliatin Yuliatin; Bagdawansyah Alqadri; Rispawati Rispawati (MANAZHIM, 2022)
This study aims to describe the implementation of personality development programs for children correctional education and the factors that influence the implementation of the coaching program personality for correctional students in LPKA class II Central Lombok.The research approach used in this research is a qualitative approach with a descriptive method. Research subjects and informants This was determined by purposive sampling technique. The data that has been collected is analyzed systematically descriptive method through data reduction steps, data presentation and conclusion drawing. The results in this study are the implementation of personality development programs for correctional students in LPKA Class II Central Lombok includes: implementation of fostering devotion to God The Almighty, awareness of the nation and state, intellectual, attitude and behavior, health physical and spiritual, legal awareness and healthy reintegration with society. Factor internal implementation of personality development includes coaching facilities, human resources people, the quality of the personality development program, the cooperative attitude of the students correctional facilities and adequate budget. External factors of the implementation of the coaching program personality, namely the cooperation with related agencies.